A finite control set model predictive control method for matrix converter with zero common-mode voltage - Wang, Lina; Dan, Hanbing; Zhao, Yue; Zhu, Qi; Peng, Tao; Sun, Yao; Wheeler, Patrick (IEEE, 2018)
In this paper a finite control set model predictive control method is presented that eliminates the common-mode voltage at the output of a matrix converter. In the predictive control process only the rotating vectors are selected to generate the output voltage and the input current in order to remove the common mode voltage. In addition, a modified four-step commutation strategy is proposed to eliminate common-mode voltage spikes caused by the conventional four-step commutation strategy based on the current direction. The proposed method reduces the computational complexity greatly compared with the enhanced space vector modulation with rotating vectors. The feasibility and operation of the proposed method are verified using experimental results. The resulting common-mode voltage is near to zero with good quality input and output converter waveforms.